Tradisi Keagamaan Masyarakat Kota Bandung di Bulan Ramadan Tahun 1990-2000 - Nugraha, Muhammad Fajar; Sulasman, Sulasman; Supendi, Usman (Historia Madania: Jurnal Ilmu Sejarah, 2018)
In a fairly long period of time in the early 20th century, there were a lot of diverse and unique traditions of the people of Bandung City to discuss. Considering that this material has not been widely discussed in scientific works. Bandung City community tradition during the month of Ramadan takes place so many habits are entrenched in the city of Bandung during the month of Ramadan. The term "Ngabuburit" has been immersed for a long time and has been passed down through its development. This study aims to find out the socio-religious conditions of the people of Bandung City and how the Ramadan Fasting Tradition in Bandung City in 1990-2000. The method used in this research is historical research methods. The research method is carried out through four stages. That is, heuristics (collection of resources), criticism (analyzing the authenticity of source credibilits), interpretation (interpretation of data) and finally historiography (historical writing). Based on the results of research on socio-religious conditions in the city of Bandung as well as urban life in other cities, the city of Bandung has multiple social problems. With this in mind, the efforts should be made to develop supporting facilities that make it convenient for the people of Bandung itself. This may not be a big problem because if seen from the place of worship, the government has provided and every year continues to grow. Of course this does not guarantee that there is no problem, but at least because every year the number of places of worship is increasing, besides the people in Bandung are increasing, they are still aware of their obligations as religious people.